Anterolateral thigh flap combined with free fascia lata graft for an adult abdominal wall defect reconstruction: a special case report - Shen, Hang-Chong; Sun, Zhong-Xin; Hu, Rui-Bin; Zhou, Dan-Ya; Huang, Tian-Xiang; Wang, Xin (Frontiers in Surgery, 2025)
Large abdominal wall defects pose significant reconstructive challenges. Congenital omphalocele persisting untreated into adulthood is exceptionally rare. We present the first documented case in China of an adult female with a giant congenital omphalocele (defect size: 13 cm × 9 cm; defined as a defect >5 cm in diameter) managed using a novel autologous technique. A combined approach utilizing a free left anterolateral thigh (ALT) with attached fascia lata and an additional harvested fascia lata strip was employed. Preoperative CT confirmed a sternal cleft, rib hypoplasia, scoliosis, and significant rectus diastasis (max 6.8 cm). The ALT flap provided soft tissue coverage, and the attached fascia lata was sutured bilaterally to the anterior rectus sheath. A separate fascia lata strip was interwoven through perforations in the rectus sheaths under tension, reducing diastasis by ∼2.5 cm. Microvascular anastomosis connected the flap pedicle to the inferior epigastric artery. Postoperative recovery was uneventful with stable vital signs, no infection, and excellent flap perfusion. At the 6-month follow-up, the abdominal contour had significantly improved. The flap exhibited moderate thickness without bulkiness, and there was no visceral protrusion in any position. The thigh donor site healed well. The reconstruction achieved sufficient strength, acceptable aesthetics, and preserved fertility potential. The free ALT flap combined with tensioned fascia lata strips represents an effective, autologous solution for complex, large abdominal wall defects, particularly in rare cases such as adult congenital omphalocele, offering robust reconstruction without synthetic materials or secondary surgery.